Fragility Fracture Incidence in Chronic Obstructive Pulmonary Disease (COPD) Patients Associates With Nanoporosity, Mineral/Matrix Ratio, and Pyridinoline Content at Actively Bone‐Forming Trabecular Surfaces. (31st October 2016) - Paschalis, Eleftherios P; Gamsjaeger, Sonja; Dempster, David; Jorgetti, Vanda; Borba, Victoria; Boguszewski, Cesar L; Klaushofer, Klaus; Moreira, Carolina A
ABSTRACT: Chronic obstructive pulmonary disease (COPD) is associated with low areal bone mineral density (aBMD) by dual‐energy X‐ray absorptiometry (DXA) and altered microstructure by bone histomorphometry and micro‐computed tomography. Nevertheless, not all COPD patients sustain fragility fractures. In the present study, we used Raman microspectroscopic analysis to determine bone compositional properties at actively forming trabecular surfaces (based on double fluorescent labels) in iliac crest biopsies from 19 postmenopausal COPD patients (aged 62.1 ± 7.3 years). Additionally, we analyzed trabecular geometrical centers, representing tissue much older than the forming surfaces. Eight of the patients had sustained fragility fractures, and 13 had received treatment with inhaled glucocorticoids. None of the patients had taken oral glucocorticoids. The monitored parameters were mineral/matrix ratio (MM), nanoporosity, and relative glycosaminoglycan (GAG), lipid, and pyridinoline contents (PYD). There were no significant differences between the glucocorticoid‐treated patients and those who did not receive any. On the other hand, COPD patients sustaining fragility fractures had significantly lower nanoporosity and higher MM and PYD values compared with COPD patients without fragility fractures. To the best of our knowledge, this is the first study to discriminate between fracture and non‐fracture COPD patients based on differences in the material properties of bone matrix. Given that these bone material compositional differences are evident close to the cement line (a major bone interface), they may contribute to the inferior bone toughness and coupled with the lower lumbar spine bone mineral density values result in the fragility fractures prevalent in these patients. © 2016 American Society for Bone and Mineral Research.